Updated Weight and Height-for Age Centiles in a Group of Predominantly Breastfed Turkish Children Aged 0-2 Years - Colak, Cemil; Camurdan, Aysu Duyan; Ergocen, Salih; Elhan, Atilla Halil; Sahin, Figen (Ortadogu Ad Pres & Publ Co, 2009)
Objective: To update the weight and height centiles for a group of predominantly breastfed children aged 0-2 years from the medium-high socioeconomic status living in Ankara. Material and Methods: The study design was prospective cohort. Between 2002 and 2004, height and weight measurements of 0-2 year-old healthy children from the medium-high socioeconomic status were recorded in definite time-intervals in the Healthy Child Clinic of Gazi University Faculty of Medicine. Height and weight percentile curves were constructed using the LMS method for boys and girls. Results: In height and weight percentile curves, a steady upward trend was detected until 24 months of age for each gender. The estimated 50(th) percentiles of height and weight were mostly higher than the 50(th) percentiles suggested by the World Health Organization (WHO) 2006 and Neyzi 1978. The 50(th) height and weight percentiles of the present study were closer to those of WHO than those of Neyzi. Conclusion: The present study reports the updated percentile values and curves for height and weight in a group of predominantly breastfed children aged 0-2 years from the medium-high socioeconomic status in Ankara. However, since the obtained data does not represent the whole country, it may be more reasonable to use the updated WHO multicenter growth reference curves.
Keywords: Child; growth; growth&development; body height; body weight changes